Nick Deocampo won the grand prix at the 9th international festival of super-8 films and video - Deocampo, Nick (Animo Repository, 1987)
Nick Deocampo of the Communication Arts Department, won the Grand Prix at the 9th International Festival of Super-8 Films and Video in Brussels, Belgium. He garnered the Jacques Brel award for his film trilogy, Oliver, Children of the Regime, and Revolutions Happen Like Refrains in a Song.